Photoinduced enhancement of a triboelectric nanogenerator based on an organolead halide perovskite. Issue 43 (27th October 2016) - Su, Li; Zhao, Zhenxuan; Li, Huayang; Wang, Ying; Kuang, Shuangyang; Cao, Guozhong; Wang, Zhonglin; Zhu, Guang
Abstract : We report a methylammonium lead triiodide (MAPbI3 ) perovskite-based photoenhanced triboelectric nanogenerator (TENG). Abstract : We report a methylammonium lead triiodide (MAPbI3 ) perovskite-based photoenhanced triboelectric nanogenerator (TENG). It features a dual working mechanism that relies on the joint properties of the photoelectric and triboelectric effects of the perovskite material. Both the photoconductivity and the surface triboelectric density of the perovskite-based composite thin film are significantly altered under solar illumination, resulting in considerable enhancement of the electrical output. The triboelectric output open-circuit voltage ( V oc ), short circuit current ( I sc ), and amount of electric charge ( Q ) were increased by 11%, 11%, and 9%, respectively, after illumination under full-sun conditions. Our work provides an approach for the enhancement of the mechanical-to-electrical conversion efficiency of the TENG by sunlight absorption.